ANALISIS PENGARUH BUDAYA PERUSAHAAN TERHADAP KINERJA KARYAWAN PADA PT BANK TABUNGAN NEGARA (PERSERO) TBK CABANG PALEMBANG - Roswaty Roswaty (JURNAL KOMPETITIF, 2021)
This study aims to determine the influence of corporate culture on the performance of employees of PT. Bank Tabungan Negara (Persero) Tbk Palembang Branch. This study involves a total sample of 58 respondents. The sampling technique used in this study is a saturated sample. In this study, the independent variable is corporate culture, and the dependent variable is employee performance. The correlation coefficient number is applied to determine the relationship between company culture and employee performance. Based on the results of these data, it can be explained that between corporate culture on employee performance variables have a very strong relationship because it has a correlation value of 0.860 (86.0%). From the calculation of the coefficient of determination (R2), it can be summarized that there is an influence of cultural variables on employee performance by 74%, and the remaining 26% is influenced by other independent variables not included in this study.